2019
DOI: 10.1007/s11302-018-9641-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the adenosinergic pathway: the indispensable part of oncological therapy in the future

Abstract: In recent years, immunotherapy has produced many unexpected breakthroughs in oncological therapy; however, it still has many deficiencies. For example, the number of patients who are unresponsive to anti-programmed death-ligand 1 (PD-L1), anticytotoxic T-like antigen-4 (CTLA4), and anti-programmed death-1 (PD1) therapies cannot be ignored, and the search for an undiscovered immunosuppressive pathway is imminent. Five decades ago, researchers found that activation of the adenosinergic pathway was negatively cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 182 publications
(222 reference statements)
0
12
0
Order By: Relevance
“…Also, the A2B receptor is related to increased resistance to doxorubicin in the treatment of BC (Table 1 ) [ 108 ]. Therefore, its inhibition decreases the growth and metastatic potential of ER negative breast tumors and TNBC, in addition to promoting a better response to chemotherapy treatment [ 101 , 122 , 123 ].…”
Section: Main Purinergic Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the A2B receptor is related to increased resistance to doxorubicin in the treatment of BC (Table 1 ) [ 108 ]. Therefore, its inhibition decreases the growth and metastatic potential of ER negative breast tumors and TNBC, in addition to promoting a better response to chemotherapy treatment [ 101 , 122 , 123 ].…”
Section: Main Purinergic Receptorsmentioning
confidence: 99%
“…It is known that CD73 is related to a worse prognosis in TNBC and HER2 positive BC [ 123 ]; therefore, studies in mice found that silencing the CD73 gene in BC cells led to a decrease in levels of focal adhesion kinase (FAK), which is related to cells adhesion and migration. The use of anti-CD73 mAb slows the growth of cancer cells and TNBC metastasis [ 102 , 221 ] to the lung [ 218 ], in addition to reducing tumor angiogenesis in mouse models with BC [ 219 ].…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…In the last 10 years, cancer research has especially focused on the role played by Ado-, CD39-, and CD73-producing ectoenzymes in immunomodulation and evasion of the antitumor immune response. In fact, inhibition of the adenosinergic pathway in the tumor microenvironment has been proposed as an indispensable alternative in oncological therapy [ 36 , 37 ]. However, large gaps in knowledge prevent the development of effective Ado-based therapies, such as the roles of redundant pathways that control ATP and Ado levels.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, increased adenosine metabolism is now recognized as a characteristic of many types of cancer. Elevated adenosine, and its metabolic precursor adenosine triphosphate (ATP), promote cancer growth and play a role in host immunosuppression in the tumor microenvironment (TME) [ 36 , 40 , 41 , 42 , 43 ].…”
Section: Cancer Incidence In Schizophreniamentioning
confidence: 99%